Concomitant presentation and surgical management of bilateral serotonin-producing carotid body tumor and thyroid carcinoma - Astrid Varela-Arzate; Carlos D. Franco-Gonzalez; Aliberth Bonilla-Salas; Osvaldo A. Gamboa-Abundis; Rafael H. Pérez-Soto; Hugo Laparra-Escareno; Javier E. Anaya-Ayala (Annals of Vascular Surgery - Brief Reports and Innovations)
Carotid body tumors (CBTs) are rare neuroendocrine neoplasms, and approximately 2% are catecholamine and dopamine producers. While CBTs may coexist with other neck neoplasms, the presence of a serotonin-producing CBT with malignancies, such as papillary thyroid carcinoma, is uncommon, with limited published data. We present the case of a 66-year-old woman with progressive weight loss who was found to have bilateral palpable neck masses. A comprehensive evaluation led to the diagnosis of a bilateral serotonin-producing carotid body tumor and papillary thyroid carcinoma. The initial surgical intervention included a total thyroidectomy and resection of the right CBT with our retrocarotid dissection technique. Eight months later, our vascular surgery team performed the resection of the contralateral CBT. At seventeen months of follow-up serotonin levels gradually decreased until reaching normal values. This case illustrates a rare clinical occurrence and successful management of bilateral serotonin-producers CBTs with papillary thyroid carcinoma.